Global flexibility of tertiary structure in RNA: Yeast tRNA(Phe) as a model system - Friederich, Marisa W. (The National Academy of Sciences, 1998)
The study of RNA structure using x-ray crystallography or NMR has yielded a wealth of detailed structural information; however, such approaches do not generally yield quantitative information regarding long-range flexibility in solution. To address this issue, we describe a solution-based method that is capable of characterizing the global flexibilities of nonhelix elements in RNA, provided that such elements are flanked by helix (e.g., bulges, internal loops, or branches). The “phased τ ratio” method is based on the principle that, for RNA molecules possessing two variably phased bends, the relative birefringence decay times depend on the flexibility of each bend, not simply the mean bend angles. The method is used to examine the overall flexibility of the yeast tRNA(Phe) core (as unmodified transcript). In the presence of magnesium ions, the tRNA core is not significantly more flexible than an equivalent length of RNA helix. In the absence of divalent ions, the tRNA core gains flexibility under conditions where its secondary structure is likely to be largely preserved. The phased τ ratio approach should be broadly applicable to nonhelix elements in both RNA and DNA and to protein–nucleic acid interactions.